Tumor budding and cell nest size are highly prognostic in laryngeal and hypopharyngeal squamous cell carcinoma: further evidence for a unified histopathologic grading system for squamous cell carcinomas of the upper aerodigestive tract - Boxberg, Melanie; Warth, Arne; Weichert, Wilko (The American journal of surgical pathology, 2019)
Squamous cell carcinoma (SCC) is the most common cancer of the head and neck region including—among others—laryngeal (LSCC) and hypopharyngeal (HSCC) subsites. LSCC/HSCC are heterogenous diseases with respect to patient outcome. Currently, tumor stage-based patient stratification is essential to pre
Gesehen am 02.09.2019